2008
DOI: 10.1185/030079907x242782
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and costs associated with anemic chronic kidney disease patients

Abstract: Health care providers can play an active role in detecting anemia early and optimizing available treatment options. Future research on the effects of erythropoiesis-stimulating agents (ESA) on patients before they need dialysis, and a cost analysis between epoetin and darbepoetin alpha, would be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 14 19 Polypharmacy was a vital component to be looked at as evidence showed that treating patients with multiple medications, ie, polypharmacy, can adversely affect patient outcomes. 14 – 16 , 19 , 21 23 …”
Section: Methodsmentioning
confidence: 99%
“… 14 19 Polypharmacy was a vital component to be looked at as evidence showed that treating patients with multiple medications, ie, polypharmacy, can adversely affect patient outcomes. 14 – 16 , 19 , 21 23 …”
Section: Methodsmentioning
confidence: 99%
“…A final relevant consideration is that nephrologists have greater experience in managing ESAs and the iron status of their patients. Increasing iron storage and availability has a positive impact on the attainment of Hb targets with erythropoietin, although the risk for hemosiderosis should be considered [38].…”
Section: Experience In Managing Iron Statusmentioning
confidence: 99%